Development Of Low Fat Fibre Rich Meatballs Using Hydrated Wheat Bran - Haq, Tarteela; Hassan Sofi, Asif; Imtiyaz Chisti, Hafsa; Sajad, Sadiya; Rafeh Ahmad, Sheikh; Salam, Ishrat (Journal of Meat Science, 2026)
The current study was aimed at optimizing the amount of fat and dietary  fibre content for the production of low fat fibre rich meatballs (locally called  as Rista). In the first experiment, different combinations of lean meat, animal  fat, and vegetable fat (T1 = 90% lean meat: 10% animal fat; T2 = 90% lean  meat: 5% animal fat: 5% vegetable fat; T3 = 90% lean meat: 10% vegetable  fat) were compared to control (T0 = 80% lean meat: 20% animal fat). Based  on physicochemical, proximate, dietary fibre content and sensory scores, T1  (90% lean meat: 10% animal fat) was found optimum for the formulation  of functional meatballs. In the second experiment, hydrated wheat bran as  dietary fibre source was incorporated at three levels (4, 8, and 12%) replacing  lean meat in the formulation of gravy-based products. 8% HWB was found  optimum for the development of functional meatballs. It was concluded that  the formulation containing 82% lean meat, 10% animal fat, and 8% hydrated  wheat bran was suitable for the preparation of functional meatballs.
Keywords: Dietary fibre; texture profile; Rista; water activity; meatballs; functional